Composition and Sensitivity of Residential Energy Consumption - Raul Jimenez; Ariel Yepez-Garcia (Inter-American Development Bank (IDB), 2016)
Understanding how energy use evolves at different stages of development is essential for reliable prospective analysis and planning. With that aim in mind, this paper examines the composition of residential energy consumption and its sensitivity to income changes, distinguishing fuel types and accounting for complete heterogeneity of the income coefficient. The focus on domestic energy use allows for the examination of fuel transition under the conceptual framework of the energy ladder and energy portfolio hypotheses, showing the increasing need for modern fuels in the household sector. The results indicate a nonlinear relationship between income and domestic energy consumption that can be attributed to two factors. First, along the income distribution, consumption of modern fuels increases, replacing traditional and transitional fuels until modern fuels drive all of the growth in domestic energy demand. Second, at the highest income levels, income elasticity starts to decrease, leading to concavity in energy consumption. That is, the income elasticity of residential energy demand follows an inverse U-shape along the world income distribution. This finding suggests that at high income levels, residential energy consumption shows satiation and net savings effects, potentially implying that energy demand does not grow forever.
hdl:11319/7798
Keywords: Q40; O13; 330; residential energy consumption; income per capita; satiation effects; income elasticity of energy demand; machine learning